Motivasi Masyarakat Bali Untuk Bekerja di Jepang - I Gusti Ayu Niken Launingtia (Jurnal Pendidikan dan Pembelajaran, 2022)
When working or doing something to be more enthusiastic, you must have a motivation, but increasing that motivation is a little difficult for some people. This research was conducted with the aim of knowing the motivation of the Balinese people to work in Japan. The object of this research is students who conduct job training at the Job Training Institute (LPK) in Ubud and Tabanan areas. The method of using the data in this study used the interview method, the observation method and the questionnaire method. The data analysis technique used is qualitative analysis technique. It can be concluded from the results of the analysis related to "Motivation of the Balinese People to Work in Japan" is to increase the motivation in each of them even before knowing or deciding to take part in training to work in Japan, but with patience to follow the training provided at LPK ( Job Training Institutes) in Bangli, Ubud and Tabanan areas, the community becomes more enthusiastic to work in Japan without coercion from outsiders, both family and friends. The Balinese people's motivation to work in Japan was seen to have greatly increased from the gradual changes when filling out the questionnaire and when being interviewed more deeply about matters related to the completed questionnaire